Asparagus azerbaijanensis, a new species of Asparagus subgen. Asparagopsis (Asparagaceae) from Iran - Hamdi, Seyed Mohammad Mahdi; Assadi, Mostafa (Phytotaxa, 2017)
Asparagus Linnaeus (1753: 313) (Asparagaceae) is a genus of about 120 species (Baker 1875). The Iranian Asparagus species have been divided into two subgenera: A. subgen. Asparagus and A. subgen. Asparagopsis Kunth (1844: 35) Baker (1875: 595) (Browicz 1990). Eleven species were recorded so far for the country (Baker 1875, Iljin 1935, Parsa 1949, Wendelbo 1964, 1985, Davis, 1984, Browicz, 1990, Hamdi & Assadi 2009, 2012, 2016). While preparing an account of Asparagaceae for Flora of Iran, a putative new species from NW of Iran was found. This was confirmed by the study of herbarium material and field work.